Digestibility, ruminal fermentation, and nitrogen balance with various feeding levels of oil palm fronds treated with Lentinus sajor-caju in goats - Hamchara, Puwadon (Asian-Australas J Anim Sci, 2018)
OBJECTIVE: This study was an attempt to investigate the effect of levels of fungal (Lentinus sajor-caju) treated oil palm fronds (FTOPF) on digestibility, rumen fermentation, and nitrogen balance in goats. METHODS: Four 16 month old male crossbred (Thai Native×Anglo Nubian) goats with initial body weights of 33.5±1.7 kg were randomly assigned according to a 4×4 Latin square design. Four levels of FTOPF were assigned for feed intake. The experimental treatments consisted of 0%, 33%, 67%, and 100% of oil palm fronds (OPF) being replaced by FTOPF. RESULTS: The results revealed that total dry matter intake and nutrient intake were not influenced (p>0.05) by the inclusion of FTOPF. However, the efficiency values of the digestibility of the dry matter, organic matter, crude protein, neutral detergent fiber, acid detergent fiber, and acid detergent lignin on FTOPF were higher (p<0.05) in treatments with 33%, 67%, and 100% of FTOPF compared with 0% of FTOPF. FTOPF feeding did not change the rumen pH, temperature, and NH(3)-N. However, the FTOPF levels did affect the total volatile fatty acid (VFA), molar proportion of acetate, propionate, butyrate, ratio of acetic (propionic acid and acetic) plus butyric (propionic acid), and production of CH(4). The totals of VFA and propionate was lower in goat fed with 0% of FTOPF than in those of the other groups (p<0.05). The amount of nitrogen retention based on g/d/animal or the percentage of nitrogen retained was the lowest the goat fed with 0% of FTOPF (p<0.05), whereas nitrogen intake, excretion, and absorption were not changed among treatments. CONCLUSION: Based on this study, FTOPF could be effectively used as an alternative roughage source in total mixed ration diets, constituting at least up to 100% of OPF.